Decisions in Economics and Finance - Ghirardato, Paolo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Decisions in Economics and Finance: A Journal of Applied Mathematics is the official publication of the Association for Mathematics Applied to Social and Economic Sciences (AMASES). It provides a specialised forum for the publication of research in all areas of mathematics as applied to economics, finance, insurance, management and social sciences. Primary emphasis is placed on original research concerning topics in mathematics or computational techniques which are explicitly motivated by or contribute to the analysis of economic or financial problems.
Keywords: Management; Operations research; Decision making; Finance; Economic theory; Econometrics; Public finance; Economic Theory/Quantitative Economics/Mathematical Methods; Econometrics; Public Finance; Finance, general; Management; Operations Research/Decision Theory